A stable and biocompatible shortwave infrared nanoribbon for dual-channel in vivo imaging - Cheng Yao; Ruwei Wei; Xiao Luo; Jie Zhou; Xiaodong Zhang; Xicun Lu; Yan Dong; Ruofan Chu; Yuxin Sun; Yu Wang; Wencheng Xia; Dahui Qu; et al. (Nature Communications)
Abstract The shortwave infrared (SWIR) region is an ideal spectral window for next-generation bioimaging to harness improved penetration and reduced phototoxicity. SWIR spectral activity may also be accessed via supramolecular dye aggregation. Unfortunately, development of dye aggregation remains challenging. We propose a crystal-aided aggregate synthesis (CAASH) approach to introduce a layer of rationality for the development of J-aggregate and the successful development of a water-soluble SWIR JV-aggregate with a bisbenzannulated silicon rhodamine scaffold (ESi5). The resulting SWIR-aggregates exhibit excellent stabilities toward organic solvents, pH, sonication, photobleaching, thiols, and endogenous oxidative species. Notably, the aggregates have a high structure-dependent melting temperature of ca. 330-335 K. In fact, the heating/annealing process can be exploited to reduce aggregation disorder. The aggregates are biocompatible and have broad potential in in vivo fluorescence and photoacoustic imaging and more.